KORELASI ANTARA HASIL TES LISAN DENGAN HASIL TES TERTULIS PADA MAHASISWA PGSD UNRAM - Itsna Oktaviyanti; Awal Nur Kholifatur Rosyidah (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to determine the correlation between oral test results with the written test results of PGSD UNRAM students. The approach used in this research is quantitative with the type of correlation research. The population was all of second semester studentsm using sampling technique of simple random sampling, the samples obtained amounted to 180. Data collection techniques used were oral tests and written tests. Data analysis techniques using descriptive statistical analysis and Product Moment correlation. The results showed that: 1) oral test results were included in both categories with an average of 79.6; (2) written test results are included in both categories with an average of 78.65; and (3) there is a correlation between the learning outcomes of oral tests with the written learning outcomes of PGSD UNRAM students. Students who understand the concept of the material, have good social studies learning outcomes between oral tests and written tests. Both types of tests can be varied implementation, according to time, conditions, and type of material to be tested.